KEMANDIRIAN ANAK USIA 4-6 TAHUN DI DESA GAYAMAN KECAMATAN BANGSAL KABUPATEN MOJOKERTO - Dwiharini Puspitaningsih (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
This research aimed to determine the independence of children age 4-6 years in Gayaman Bangsal Mojokerto. This research use a descriptive study, the variable is the independence of children aged 4-6 years as many as 78 children. Sampling used nonprobability sampling technique by consecutive sampling and using observation sheet. The results showed that the child can be independently as many as 67 85.90% and there are 11 children who couldn’t be independently (14.10%). The child who get dressed independently from first observation of question as many as 72 (92.30%) independent child, and not independent as many as 6 children ( 7.70%), the child who could eating independently as many as 82.05% (64 children), and 14 children are not independent (17, 95%), the child's who have independence in toileting of 7th observation are 61 children (78.20%), which is not independently as many as 17 children (21.80% ), the child's independence in terms of playing from 10th observations to 74.35% (58 children) and there are 20 children (25.65%). This occurs because of genetic and environmental factors that greatly affect the child's independence, the conclusions of this study is that the independence of children aged 4-6 years in Pekuwon Bangsal Mojokerto most of respondents have independence attitude, because of that parents are expected to pay more attention to the development of the child's independence.